2012
DOI: 10.1021/jp2123136
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Permeation across the OmpF Channel: Modulation of the Affinity Site in the Presence of Magnesium

Abstract: We characterize the rate-limiting interaction of the antibiotic enrofloxacin with OmpF, a channel from the outer cell wall of Escherichia coli . Reconstitution of a single OmpF trimer into planar lipid membranes allows measurement of the ion current through the channel. Penetration of antibiotics causes ion current blockages, and their frequency allows a conclusion on the kinetics of channel entry and exit. In contrast to other antibiotics, enrofloxacin is able to block the OmpF channel for several millisecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 28 publications
7
82
0
Order By: Relevance
“…Solvent-free Lipid Bilayer Measurements-Reconstitution experiments and noise analysis were performed as described previously in detail (19). The Montal and Muller technique was used to form phospholipid bilayer using 1,2-diphytanoyl-snglycero-3-phosphocholine (Avanti Polar Lipids) (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent-free Lipid Bilayer Measurements-Reconstitution experiments and noise analysis were performed as described previously in detail (19). The Montal and Muller technique was used to form phospholipid bilayer using 1,2-diphytanoyl-snglycero-3-phosphocholine (Avanti Polar Lipids) (23).…”
Section: Methodsmentioning
confidence: 99%
“…The authors suggested that, in contrast to the obvious exclusion due to reduced channel size, effects such as changes in the electric field at the constriction zone might have an impact on the channel permeability (17). Recent computational and experimental studies also suggested that the electrostatic profile inside the channel might play a major role in transit of polar molecules (18,19). Subsequently, the internal electrostatics of the mutant porins (OmpC20 and OmpC33) were analyzed in the absence of any antibiotic or metabolite, using water as a probe to sense the internal electric field (20).…”
mentioning
confidence: 99%
“…Modelling revealed that Mg 2+ can bind strongly in the eyelet region of OmpF, as shown in Fig. 3, reversing the net charge of this region [21]. As a consequence, enrofloxacin can penetrate with an optimal orientation for permeation, his carboxylic group entering first, increasing the association rate and the total flux, as measured by electrophysiology.…”
Section: Molecular Modellingmentioning
confidence: 87%
“…In contrast, addition of 5 mM MgCl 2 into the buffer change completely the spectra, many ion current blockages are visible (Fig. 2 bottom) [21]. The example of Fig.…”
Section: Approaches To Measure Influxmentioning
confidence: 93%
“…It also showed that L3 flexibility affected a change in pore cavity [25]. MD simulations were also successfully used to observe the solute (such as antibiotics) passage through OmpF in comparison with experiments [2, 15,[29][30][31]. OmpF are computationally well studied whereas few computational studies on OmpC are found.…”
Section: Introductionmentioning
confidence: 99%